Resilient Communities: A Novel Workflow - Carta, Silvio; Pintacuda, Luigi; Owen, Ian Wyn; Turchi, Tommaso (Frontiers in Built Environment, 2021)
This study presents a novel workflow to define how Zero Carbon communities can be analysed and improved through the optimisation of sustainable design principles through quantitative methods. Our model analyses successful sustainable communities (e.g. Gui et al. 2018, Boswell et al. 2019, Shandiz et al. 2021) extracting information about daily routines (commuting, working, use of buildings etc.). From these routines, we infer a set of key successful aspects based on location, density and proximity. We then model a resilient community and analyse it using a combination of clustering techniques to find patterns and correlations in the success of existing communities. The proposed workflow is applied to the city of Copenhagen as a case study. The aim of the proposed model is to suggest to designers and city-level policy makers improvements (with manipulation of variables like density, proximity and location of urban typologies) to help them to achieve different levels of sustainable goals as set out by the United Nations Global Challenges including integration (Stafford-Smith et al. 2017), inclusiveness (Filho et al 2019), and resilience (Caputo et al. 2015).